Study of the first ecosystem with legal personality in Europe: analysis in the light of the international obligation to protect and comparative law - Gutiérrez Castillo, Víctor Luis (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Currently, a number of countries recognise or grant to nature or a specific ecosystems (rivers, forests, etc.) the status of Legal Personhood in order to protect and conserve the environment. This recognition has been carried out not only by law, but also through the judgements of the higher courts. Spain was the first country on the European continent and in the Mediterranean region to introduce this new protection mechanism in its legal system. In this article, we will study this case on the basis of Spain’s international commitments (in particular the obligation to protect) and comparative law. In this regard, special attention will be paid to the legal and jurisprudential practice followed in other countries where rights to nature have also been recognised.
Keywords: Legal Personhood; Legal Environmental Protection; Nature Rights; international obligation to protect; comparative law